De novo variants in MAST4 related to neurodevelopmental disorders with developmental delay and infantile spasms: Genotype-phenotype association - Zhang, Xi; Xiao, Neng; Cao, Yang; Peng, Ying; Lian, Aojie; Chen, Yuanlu; Wang, Pengchao; Gu, Weiyue; Xiao, Bo; Yu, Jing; Wang, Hua; Shu, Li (Frontiers in Molecular Neuroscience, 2023)
Objective This study aims to prove that the de novo variants in MAST4 gene are associated with neurodevelopmental disorders (NDD) with developmental delay (DD) and infantile spasm (IS) and to determine the genotype-phenotype correlations. Methods Trio-based exome sequencing (ES) was performed on the four families enrolled in this study. We collected and systematically reviewed the four probands’ clinical data, magnetic resonance images (MRI), and electroencephalography (EEG). We also carried out bioinformatics analysis by integrating published exome/genome sequencing data and human brain transcriptomic data. Results We described four patients whose median age of seizure onset was 5 months. The primary manifestation was infantile spasms with typical hypsarrhythmia on EEG. Developmental delays or intellectual disabilities varied among the four individuals. Three de novo missense variants in MAST4 gene were identified from four families, including chr5:66438324 (c.2693T > C: p.Ile898Thr) z, chr5:66459419 (c.4412C > T: p.Thr1471Ile), and chr5:66462662 (c.7655C > G:p.Ser2552Trp). The missense variant p.Ile898Thr is mapped to the AGC-kinase C-terminal with phosphatase activity. The other variant p.Ser2552Trp is located in a phosphoserine-modified residue which may affect cell membrane stability and signal transduction. Besides, the variant p.Thr1471Ile is a recurrent site screened out in two unrelated patients. Compared to private mutations (found only in a single family or a small population) of MAST4 in the gnomAD non-neuro subset, all de novo variants were predicted to be damaging or probably damaging through different bioinformatic analyses. Significantly higher CADD scores of the variant p.Thr1471Ile indicate more deleteriousness of the recurrent site. And the affected amino acids are highly conserved across multiple species. According to the Brainspan Atlas database, MAST4 is expressed primarily in the mediodorsal nucleus of the thalamus and medial prefrontal cortex during the prenatal period, potentially contributing to embryonic brain development. Conclusion Our results revealed that the variants of MAST4 gene might lead to neurodevelopmental disorders with developmental delay and infantile spasm. Thus, MAST4 variants should be considered the potential candidate gene in patients with neurodevelopmental disorders clinically marked by infantile spasms.